The Effect of Service and Customer Satisfaction on Customer Loyalty at MSMEs in Medan Selayang District - Adam Sarifudin; Annisa Sanny (Journal of Research in Social Science and Humanities, 2024)
This study aims to analyse the effect of service and customer satisfaction on customer loyalty. The object of research is MSMEs in Medan Selayang District. This type of research is descriptive research with a quantitative approach. The research method is multiple linear regression analysis. The sample in this study were 98 respondents. The results showed that simultaneously service and customer satisfaction had an effect on customer loyalty. While partially service has a significant positive effect on customer loyalty. Customer satisfaction has a significant positive effect on loyalty. Construbis the influence of these variables is 38.8%.